Does periampullary diverticulum affect ERCP cannulation and post-procedure complications? an up-to-date meta-analysis - Peilei Mu,; Peilei Mu,; Ping Yue,; Ping Yue,; Fangwei Li,; Yanyan Lin,; Yanyan Lin,; Ying Liu,; Wenbo Meng,; Wenbo Meng,; Wenbo Meng,; Wence Zhou,; et al. (Turkish Journal of Gastroenterology, 2020)
Research conclusions differ on the impact of periampullary diverticulum (PAD) on endoscopic retrograde cholangiopancreatography (ERCP). An up-to-date meta-analysis evaluated the role of PAD in ERCP, especially in terms of cannulation failure and early complications. A comprehensive literature search was performed. All statistical analyses were carried out with the Review Manager 5.3 software. Horizontal lines represented a 95% confidence interval (CI) and the area of each square in forest plots. Twenty-six studies including 23 826 patients with or without PAD who underwent ERCP were evaluated. PAD was associated with an increase in the overall cannulation failure rate (RR=1.46, 95% CI: 1.27-1.67; p<.00001), but in the subgroup of studies performed post-2000, PAD was irrelevant to cannulation failure (RR=1.16, 95% CI: 0.96–1.41; p=0.12). In overall analyses, PAD was also associated with a high risk of ERCP-related pancreatitis (RR=1.32, 95% CI: 1.10-1.59; p=0.003), perforation (RR=1.73, 95% CI: 1.06-2.82; p=0.030), and bleeding (RR=1.48, 95% CI: 1.13–1.93; p=0.005). The presence of PAD increased the overall cannulation failure rate, but not the rate post-2000. PAD also affected the occurrence of early pancreatitis, perforation, and bleeding.Cite this article as: Mu P, Yue P, Li F, et al. Does periampullary diverticulum affect ERCP cannulation and post-procedure complications? an up-to-date meta-analysis. Turk J Gastroenterol 2020; 31(3): 193-204.